The Minister of Education and Culture's Award for Visual Art - The First Decade. - Hammer, Zvulun; Heller, Sorin (Tel Aviv : Tel Aviv Museum of Art, 1996)
Ben-David, Arnon ; Zvi, Asaf Ben ; Alkara, Ovadia ; Avny, Shimon ; Bar-El, Ido ; Berest, Dganit ; Blich, Bilu ; Borkowsky, Joshua ; Gan, Pinchas Cohen ; David, Nurit ; Dominey, Drora ; Dorchin, Yaacov ; Eliasaf, Smadar ; Eshel-Gershuni, Bianca ; Gechtman, Gideon ; Gershuni, Moshe ; Getter, Tamar ; Geva, Tsibi ; Ginton, David ; Goldstein, Zvi ; Golombek, Itshak ; Gross, Michael ; Heiman, Michal ; Jano, Jack ; Kantor, Zvi ; Klasmer, Gabi ; Levin, Yudith ; Levy, Pamela ; Livneh, Yitzhak ; Maor, Haim ; Mishori, Jacob ; Na'aman, Michal ; Nishri, Miri ; Or-Ner, Dov ; Pichhadze, Meir ; Rantzer, Philip ; Reeb, David ; Rikman, Tamara ; Sack, Daniel ; Salama, Mani ; Schwartz, Buky ; Spitzer, Serge ; Yekutiel, Rolanda Teicher ; Tevet, Nahum ; Tolkovsky, Zvi ; Uri, Aviva ; Yacoby, Dorrit ; Yardeni, Yehezkiel
The Minister of Education and Culture's Award for Visual Art - The First Decade, Tel Aviv Museum of Art, Tel Aviv. Opening Exhibition: 5 September 1996
Engels & Hebreeuws
kunstcatalogus
Keywords: Israel